2020
DOI: 10.9734/ajrb/2020/v6i430126
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Minerals, Heavy Metals and Amino Acids Compositions of the Seeds and Juice of Cucumis metuliferus

Abstract: The aim of this study was to compare the minerals, heavy metals and amino acids compositions of the seeds and juice of Cucumis metuliferus. The minerals and heavy metals content were evaluated using FS240AA agilent atomic absorption spectrometer according to the method of American Public Health Association while the amino acids content was evaluated using High Performance Liquid Chromatography (HPLC). From the mineral analysis, concentrations of calcium (23.416 ppm), aluminum (0.094 ppm), manganese (0.242 ppm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Another study that demonstrated the neuroprotective action of this plant presented the chemical composition of the fruits from Hby local farm located at Cinfães, Douro, Portugal, with smaller concentrations of gallic acid (11.7 ± 0.6 mg/100 g), p-coumaric acid (2.86 ± 0.14 mg/100 g), protocatechuic acid (7.69 ± 0.38 mg/100 g), (+)-catechin (4.86 ± 0.24 mg/100 g), and (-)-epicatechin (4.58 ± 0.23 mg/100 g) [63]. Several studies on the African species of C. metuliferus also highlighted the presence of a wide range of vitamins (vitamin A 198.51 mg/mL, B6 835.00 mg/mL, B12 0.10 mg/mL, C 682.00 mg/mL, D 5.28 mg/mL, E 0.42 mg/mL) [64,65] and minerals (Ca, Al, Mg, Zn, K) [22,64,66].…”
Section: Identification Of Bioactive Compounds By Hplcmentioning
confidence: 99%
“…Another study that demonstrated the neuroprotective action of this plant presented the chemical composition of the fruits from Hby local farm located at Cinfães, Douro, Portugal, with smaller concentrations of gallic acid (11.7 ± 0.6 mg/100 g), p-coumaric acid (2.86 ± 0.14 mg/100 g), protocatechuic acid (7.69 ± 0.38 mg/100 g), (+)-catechin (4.86 ± 0.24 mg/100 g), and (-)-epicatechin (4.58 ± 0.23 mg/100 g) [63]. Several studies on the African species of C. metuliferus also highlighted the presence of a wide range of vitamins (vitamin A 198.51 mg/mL, B6 835.00 mg/mL, B12 0.10 mg/mL, C 682.00 mg/mL, D 5.28 mg/mL, E 0.42 mg/mL) [64,65] and minerals (Ca, Al, Mg, Zn, K) [22,64,66].…”
Section: Identification Of Bioactive Compounds By Hplcmentioning
confidence: 99%
“…The fruit is highly sought after by people in Kalahari Desert as a source of water [15] and a good source of energy with low caloric value. From studies it was shown that the juice contains essential minerals and amino acids [16]. Therefore, in addition to studies done so far, the phytochemical and vitamin content of the juice were investigated in order to ascertain its therapeutic and nutritional usefulness.…”
Section: Introductionmentioning
confidence: 99%